Summary Record of Discussions of the National Development Council (NDC) Meetings Five Decades of Nation Building (Fifty NDC Meetings) Vol - IV (36th To 44th Meetings) - Planning Commission (Planning Commission, 1982)
Welcoming the Members to the meeting of the National Development Council, Shri S. B. Chavan, Minister of Planning expressed satisfaction at the over all progress made in the first two years of the Sixth Five Year Plan. Production of food grains, which had declined sharply in 1979-80, rose to 130 million tonnes in 1980-81 and was expected to reach 134 million tonnes in 1981-82. Industrial production was expected to show an increase of more than 8 per cent in 1981- 82 as against 4 per cent in the preceding year. Capacity utilisation in major industries had gone up and the infrastructure showed a sustained improvement. There was a sharp decline in the rate of inflation in terms of wholesale prices. National income had increased by 7.5 per cent in 1980-81 and was likely to go up further by 4.5 per cent in 1981 -82. Thus, the average growth rate for the first two years of the Sixth Plan was about 6 per cent which was higher than the annual growth rate of 5.2 per cent envisaged in the Sixth Plan.
Government of India Planning Commission
Government of India Planning Commission